Funkce polovětných vazeb ve španělském textu a jejich ekvivalenty v češtině - Paukeje, Josef (Jihočeská univerzita, 2011)
Tato diplomová práce je rozdělena na teoretickou a praktickou část a zabývá se výskytem polovětných konstrukcí tvořených některým z neosobních slovesných tvarů ve španělském jazyce a volbou jejich ekvivalentů při překladu do češtiny. Cílem této práce je poskytnout přehled vlastností, zvláštností a dalších poznatků o polovětných konstrukcích ze španělsky a česky psaných zdrojů. Široké spektrum gramatik, publikací a skript, včetně dvoujazyčného elektronického korpusu literárních děl, přináší nejen velké množství informací o těchto konstrukcích, ale také rozbor volených jazykových prostředků při překladu z jednoho jazyka do druhého a vyhodnocení získaných údajů.
Function of Infinitival and Participal Clauses in Spanish Texts and their Czech Conterparts.
Keywords: polovětné konstrukce; gerundium; participium; infinitiv; ekvivalenty; korpus; překlad; This graduation theses (thesis) is divided into theoretical and practical part and researches the occurrence of these constructions made by some of the impersonal verbal forms in spanish language and the selection of their equivalents while translating to czech language. The goal of this thesis is to provide a summary of qualities; particularities and other pieces of knowledge of semi-sentential constructions from various czech written and spanish written sources. A large spectra of grammatical books; publications and scripts including a bilingual electronical corpus of literary pieces brings not only many information of mentioned constructions but also an analysis of selected linguistic resources which are needed to their translation from one language to another. The data evaluation is included as well.